In vivo hypoglycemic study of Manilkara zapota leave and seed extracts - Saikat Ranjan Paul (Bangladesh Journal of Pharmacology, 2015)
The hypoglycemic activity of pet-ether extracts of leaves and methanol extracts of seeds of Manilkara zapota was evaluated in the study. The oral glucose tolerance test was performed in mice treated with 2 mg/kg glucose solution and the blood glucose level was determined after 15, 30, 60, 90 and 120 min of administration. Alloxan (70 mg/kg) was injected intravenously to induce diabetes in mice. The hypoglycemic study was carried out 7 days. In glucose tolerance test all extracts achieved significant p values (p<0.0001) at 60, 90 and 120 minutes compared to the glucose control. In hypoglycemic study all extracts started to reduce the blood glucose level rapidly even starting from the 2nd day of treatment and significant p values (p<0.0001) were achieved. So, the study evinced the hypoglycemic potency of the leave and seed extracts of M. zapota.